The Important Role and Requirements of Primary School Teachers in the Development of Children's Knowledge and Potential (Eurasian Scientific Herald, 2022)
It is the duty of every young generation in our country to get the right education, grow and contribute to the development of our country. I'm not mistaken in saying that the biggest task is with teachers. It is the duty of every educator to direct the child from an early age to think correctly, to form the right worldview. In this article, I thought about the role of primary school teachers in our society and the methods they should use